The Persistence of Doubt after Descartes - Sánchez de León Serrano, José María (Estudios de Filosofía, 2013)
How it is to be understood that one of the most epoch-defining innovations of Cartesian thought, i. e., methodic doubt, has not been adopted by Descartes’ immediate philosophical posterity? This paper investigates the reasons for this supposed disappearance of doubt in the philosophies of Spinoza and Leibniz by means of a reexamination of the role of doubt in Descartes’ Meditations. Starting from a characterization of the Cartesian project as a search for the ground, the paper shows that Descartes’ interpretation of immediate reality in terms of representation is actually the apotheosis of a more ancient view that conceives the totality of being as contingent and vain. Thus, doubt is not a free suspension of judgement, but the inevitable irresolution that results from the lack of ontological solidity that is a feature of immediate reality when interpreted as image or representation. It is then shown that postcartesian thought actually does not dismiss doubt, but incorporates it as a basic assumption, which explains why there is no definite place for it in discourse. The further development of modern thought can, in crucial ways, be explained by means of this implicit assimilation of doubt and its consequences.